2018
DOI: 10.1111/jar.12554
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management of health by people with intellectual and developmental disabilities

Abstract: Background Self‐management of health includes people with intellectual and developmental disabilities (IDD) playing a key role in health management in collaborating with healthcare professionals. Methods This study analysed data from Personal Outcome Measures® surveys (n = 1,341) to explore self‐management of health. We had the following research questions: Who is most likely to be supported to self‐manage their health? How does being supported to self‐manage impact different areas of health? and How does bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Thus, long‐term services and supports funding must reflect and recognize the vital role organizations play in facilitating optimal health of people with IDD. In the meantime, organizations can implement cost‐effective and simple programs, such as supporting people to self‐manage their health (Friedman, Rizzolo, & Spassiani, ), in order to improve the health and quality of life of people with IDD.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, long‐term services and supports funding must reflect and recognize the vital role organizations play in facilitating optimal health of people with IDD. In the meantime, organizations can implement cost‐effective and simple programs, such as supporting people to self‐manage their health (Friedman, Rizzolo, & Spassiani, ), in order to improve the health and quality of life of people with IDD.…”
Section: Resultsmentioning
confidence: 99%
“…BIPOC with intellectual and developmental disabilities who had full/plenary guardianship had fewer quality of life outcomes present than BIPOC with intellectual and developmental disabilities who had independent decision‐making – did not have guardianship – regardless of their other demographics, including support needs. Research indicates disparities for people with disabilities with full/plenary guardianship are not uncommon (Friedman, 2019b, 2021; Friedman et al, 2018; Friedman & VanPuymbrouck, 2018). Not only does research suggest people with full/plenary guardianship receive fewer organisational supports to facilitate their quality of life than people with independent decision‐making (Friedman, 2019b, 2021; Friedman et al, 2018; Friedman & VanPuymbrouck, 2018), guardianship in the United States is often applied in a broad sweeping manner, resulting in a widespread restriction on people's rights (Salzman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates disparities for people with disabilities with full/plenary guardianship are not uncommon (Friedman, 2019b, 2021; Friedman et al, 2018; Friedman & VanPuymbrouck, 2018). Not only does research suggest people with full/plenary guardianship receive fewer organisational supports to facilitate their quality of life than people with independent decision‐making (Friedman, 2019b, 2021; Friedman et al, 2018; Friedman & VanPuymbrouck, 2018), guardianship in the United States is often applied in a broad sweeping manner, resulting in a widespread restriction on people's rights (Salzman, 2011). Given full/plenary guardianship often results in significant rights restrictions, it is not surprising that BIPOC with intellectual and developmental disabilities with full/plenary guardianship had a lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to understand the lived experience, and its impact on recovery care pathways, should be key drivers for clinicians supporting people with mental health conditions (Farr et al, 2019, Hughes et al, 2020, Simpson et al, 2016. However Friedman et al (2018) reported that people with psychiatric conditions are still unlikely to have an active role in their treatment and care decision making. Despite the intention for services to move to co-production, the patient voice in this population is rarely described in regard to dysphagia and mealtime experiences.…”
Section: Inclusive Approaches In Mental Health and Dysphagiamentioning
confidence: 99%